IMPLEMENTATION OF THE DETAINEE AND INMATE CARE FUNCTION AT THE BARRU CLASS IIB DETENTION CENTER IN THE PERSPECTIVE OF LAW NUMBER 22 OF 2022 - Amsar Amir; Khaerul Mannan; Muhammad Natsir; Bakhtiar Tijjang; Muhammad Sabir Rahman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the implementation of the care function for detainees and prisoners at the Class IIB Barru Detention Center based on the provisions of Law Number 22 of 2022 concerning Corrections. The analysis focuses on three main aspects: the fulfillment of basic rights in the form of health and nutritional needs, rehabilitation programs, and protection for vulnerable groups. The results show that the detention center has attempted to carry out its care function through basic health services, food distribution, and coaching activities, although various structural limitations limit the quality of services. Significant overcapacity conditions impact the level of environmental health, the effectiveness of rehabilitation programs, and meeting the special needs of inmates, especially those with disabilities and chronic illnesses. Limited infrastructure and the number of health workers and correctional officers exacerbate challenges in health maintenance and management of residential space. The study's conclusion confirms that the implementation of care has not fully met the mandate of the law due to high pressure on detention capacity. Therefore, improvements in facilities, strengthening human resources, and ongoing policy support are needed to optimally implement humanitarian principles in correctional facilities.